Circadian variation in witnessed out of hospital cardiac arrest - Soo, L (2000)
OBJECTIVES—To examine the effect on circadian variation of out of hospital cardiac arrest according to the underlying aetiology and presenting rhythm of arrest, and to explore strategies that might help to improve survival outcome using circadian variation. DESIGN—Population based retrospective study. SETTING—County of Nottinghamshire with a total population of 993 914 and an area of 2183 km(2). SUBJECTS—Between 1 January 1991 and 3 December 1994, all witnessed cardiac arrests attended by the Nottinghamshire Ambulance Service, of which 1196 patients had a cardiac cause for their arrest (ICD, 9th revision, codes 390-414 and 420-429) and 339 had a non-cardiac cause. RESULTS—The circadian variation of the cardiac cases was not significantly different from that of non-cardiac cases (p = 0.587), even when adjusted for age, sex, or presenting rhythm of arrest. For cardiac cases, the circadian variation of those who presented with ventricular fibrillation was significantly different from those presenting with a rhythm other than ventricular fibrillation (p = 0.005), but was similar to the circadian variation of bystander cardiopulmonary resuscitation (p = 0.306) and survivors (p = 0.542). Ambulance response time was also found to have a circadian variation. CONCLUSIONS—There is a common circadian variation of out of hospital cardiac arrest, irrespective of underlying aetiology, where the presenting rhythm is other than ventricular fibrillation. This is different from the circadian variation of cases of cardiac aetiology presenting with ventricular fibrillation. The circadian variation of ventricular fibrillation, and consequently survival, may be affected by the availability of bystander cardiopulmonary resuscitation and the speed of ambulance response.   Keywords: out of hospital; cardiac arrest; circadian variation